Skip to content

Commit

Permalink
update
Browse files Browse the repository at this point in the history
  • Loading branch information
pitmonticone committed Apr 15, 2024
1 parent a09726a commit 1a26030
Show file tree
Hide file tree
Showing 2 changed files with 6 additions and 6 deletions.
2 changes: 1 addition & 1 deletion blueprint/src/chapters/0-introduction.tex
Original file line number Diff line number Diff line change
Expand Up @@ -68,7 +68,7 @@ \chapter{Introduction}
Since $\eta$ corresponds to a third root of unity, we have that $\eta^3 = 1$,
which implies that $\eta^2 = \eta^{-1}$.
Since $\eta$ corresponds to a root of the equation $x^2 + x + 1 = 0$, then $\eta^2 = -1 - \eta$.
Substituting back, we have that $\lambda^2 = (-1 - \eta) - 2\eta + 1 = -3\eta$.
Substituting back, we have that $\lambda^2 = (-1 - \eta) - 2\eta + 1 = s-3\eta$.
\end{proof}

\begin{theorem}
Expand Down
10 changes: 5 additions & 5 deletions blueprint/src/chapters/2-case2.tex
Original file line number Diff line number Diff line change
Expand Up @@ -13,7 +13,7 @@ \chapter{Case 2}
\end{lemma}
\begin{proof}
\leanok
Since $3 \divides a^3 + b^3 = c^3$, then $3 \divides c$. \\
Since $3 \divides a^3 + b^3 = c^3$, then $3 \divides c$.
Then $3 \divides gcd(a,b,c)$.
\end{proof}

Expand All @@ -29,7 +29,7 @@ \chapter{Case 2}
\end{lemma}
\begin{proof}
\leanok
Since $3 \divides c^3 - a^3 = b^3$, then $3 \divides b$. \\
Since $3 \divides c^3 - a^3 = b^3$, then $3 \divides b$.
Then $3 \divides gcd(a,b,c)$.
\end{proof}

Expand All @@ -44,7 +44,7 @@ \chapter{Case 2}
\end{lemma}
\begin{proof}
\leanok
Since $3 \divides c^3 - b^3 = a^3$, then $3 \divides a$. \\
Since $3 \divides c^3 - b^3 = a^3$, then $3 \divides a$.
Then $3 \divides gcd(a,b,c)$.
\end{proof}

Expand Down Expand Up @@ -184,10 +184,10 @@ \chapter{Case 2}
lmm:lambda_not_dvd_two}
Since $\lambda \notdivides a$, then
$\lambda^4 \divides a^3 - 1 \lor \lambda^4 \divides a^3 + 1$ by
\Cref{lmm:lambda_pow_four_dvd_cube_sub_one_or_add_one_of_lambda_not_dvd}. \\
\Cref{lmm:lambda_pow_four_dvd_cube_sub_one_or_add_one_of_lambda_not_dvd}.
Since $\lambda \notdivides b$, then
$\lambda^4 \divides b^3 - 1 \lor \lambda^4 \divides b^3 + 1$ by
\Cref{lmm:lambda_pow_four_dvd_cube_sub_one_or_add_one_of_lambda_not_dvd}. \\
\Cref{lmm:lambda_pow_four_dvd_cube_sub_one_or_add_one_of_lambda_not_dvd}.
We proceed by analysing each case:
\begin{itemize}
\item Case $\lambda^4 \divides a^3 - 1 \land \lambda^4 \divides b^3 - 1$.
Expand Down

0 comments on commit 1a26030

Please sign in to comment.